Successful anti-PD-1 therapy in metastatic endometrial cancer with microsatellite instability: a case report - T. T. Andabekov; M. K. Rodina; G. A. Raskin; K. G. Cham; I. O. Rutkin (Опухоли женской репродуктивной системы)
High efficacy of anti-PD-1 therapy has been shown in malignant tumors with mismatch repair deficiency. According to the literature review, mismatch repair deficiency is determined in 20–40 % of all endometrial cancer cases and up to 48 % of its endometrioid subtype. We report the short review of the recent literature and the case of durable partial response on pembrolizumab immunotherapy in a patient with a metastatic endometrioid adenocarcinoma with MMR-deficiency progressed on 2 chemotherapy lines. Partial response was achieved after 6th course, treatment was stopped after 8th course. Patient is on follow-up without any anticancer treatment for 11 months. Partial response lasts for 13 months, with further reduction in tumor size. The treatment was well tolerated without adverse events.